Elucidation of the Synergistic Effect of Dopants and Vacancies on Promoted Selectivity for CO2 Electroreduction to Formate. Issue 2 (30th November 2020) - Li, Zhongjian; Cao, Ang; Zheng, Qiang; Fu, Yuanyuan; Wang, Tingting; Arul, K. Thanigal; Chen, Jeng‐Lung; Yang, Bin; Adli, Nadia Mohd; Lei, Lecheng; Dong, Chung‐Li; Xiao, Jianping; et al.
Abstract: Sn‐based materials are identified as promising catalysts for the CO2 electroreduction (CO2RR) to formate (HCOO − ). However, their insufficient selectivity and activity remain grand challenges. A new type of SnO2 nanosheet with simultaneous N dopants and oxygen vacancies ( V O ‐rich N‐SnO2 NS) for promoting CO2 conversion to HCOO − is reported. Due to the likely synergistic effect of N dopant and V O, the V O ‐rich N‐SnO2 NS exhibits high catalytic selectivity featured by an HCOO − Faradaic efficiency (FE) of 83% at − 0.9 V and an FE of > 90% for all C1 products (HCOO − and CO) at a wide potential range from −0.9 to − 1.2 V. Low coordination Sn–N moieties are the active sites with optimal electronic and geometric structures regulated by V O and N dopants. Theoretical calculations elucidate that the reaction free energy of HCOO* protonation is decreased on the V O ‐rich N‐SnO2 NS, thus enhancing HCOO − selectivity. The weakened H* adsorption energy also inhibits the hydrogen evolution reaction, a dominant side reaction during the CO2RR. Furthermore, using the catalyst as the cathode, a spontaneous Galvanic Zn‐CO2 cell and a solar‐powered electrolysis process successfully demonstrated the efficient HCOO − generation through CO2 conversion and storage. Abstract : A novel SnO2 nanosheet catalyst presents a possible synergistic effect of N dopants and oxygen vacancies on the activity and selectivity for CO2 electroreduction to formate. Low‐coordination Sn–N moieties with optimal N dopants and O vacancies are identified as active sites with intrinsically enhanced activity.